2017
DOI: 10.4102/sajhrm.v15i0.920
|View full text |Cite
|
Sign up to set email alerts
|

Organisational change and the psychological contract at a pharmaceutical company

Abstract: Orientation: Over a period of 6 years, a South African pharmaceutical company had been involved in several mergers and acquisitions. These changes had proved difficult for staff and staff attrition had risen.Research purpose: The objective of the study was to explore the perceptions of senior managers about the impact of change on the psychological contract. The sub-objectives were to determine what organisational factors contribute to changes in the psychological contract during periods of change, and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Employees who accept the change also feel that their psychological contract has been replaced by a new one. Psychological contract breach can occur during periods of organizational change (Magano and Thomas, 2017). This study has reported that psychological contract breach is low in the case of the taken merger.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Employees who accept the change also feel that their psychological contract has been replaced by a new one. Psychological contract breach can occur during periods of organizational change (Magano and Thomas, 2017). This study has reported that psychological contract breach is low in the case of the taken merger.…”
Section: Discussionmentioning
confidence: 77%
“…This study has reported that psychological contract breach is low in the case of the taken merger. Research has shown that lack of communication during mergers and acquisitions to be a major reason for the development of PCB (Magano and Thomas, 2017). Communication strategies need to be given importance to strengthen the psychological contract of employees during organizational change (Magano and Thomas, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, they are afraid of excessive control as a result of the implementation of a new management tool, but on the other, they feel motivated to improve and increase their performance in a work environment where trust and respect prevail and commitment is rewarded with positive feedback from their direct supervisors. Thus, the success of implementation and management of changes depends mainly on the perception of the employees, while their reactions to changes differ due to personal experience, levels of motivation, socio-demographic characteristics, knowledge, values and behavioral models (Furxhi et al 2016;Magano & Thomas 2017). It is essential to perceive controlling not only in terms of its economic but also psychological aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the global M&A market is referred to as the market for corporate control, which is the competition to ensure that whoever ultimately uses companies and their resources most successfully takes control of them (Jensen, 1996;Jensen & Ruback, 1983;Mueller-Stewens, 2016a). Business combinations, such as M&As, mean major and critical organisational changes for the organisations and employees concerned (Holland & Scullion, 2019;Joshi, Sanchez & Mudde, 2020;Magano & Thomas, 2017;Senior, Fearon, Mclaughlin & Manalsuren, 2017), especially those being acquired, due to the dominance and decision-making power of a larger company acquiring a smaller one. In people-driven professional services companies delivering knowledgeintensive services, including project management, planning and consulting, people are the most important factor in production, and executives have a unique role to play (Hitt, Bierman, Shimizu & Kochhar, 2001;Kaiser & Ringlstetter, 2011;Suseno & Pinnington, 2017).…”
Section: Introduction To the Researchmentioning
confidence: 99%